2013
DOI: 10.1002/ejoc.201201739
|View full text |Cite
|
Sign up to set email alerts
|

The Ant‐Pro Reverse‐Turn Motif. Structural Features and Conformational Characteristics

Abstract: This article details the characteristic conformational features of the Ant‐Pro reverse turn ― a folded pseudo β‐turn motif that displays a closed nine‐membered‐ring hydrogen‐bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained β‐amino acid), and proline (Pro; a constrained α‐amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 93 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…[47] This structure requires only the mixed b/a-dipeptide to display the closed hydrogen-bonded network (Figure 7 a). To our knowledge, 10 a represents a very rare example of a short sequence showing this kind of pseudo b-turn, [48] although it was observed in linear oligomers composed of repetitive a/b-units (e.g., Figure 7 c, d). This structure is in contrast to native bturns (Figure 7 b), which involve four residues to form the hydrogen-bonded structure in the opposite direction (residues 17 !4).…”
Section: Conformational Analysismentioning
confidence: 97%
See 3 more Smart Citations
“…[47] This structure requires only the mixed b/a-dipeptide to display the closed hydrogen-bonded network (Figure 7 a). To our knowledge, 10 a represents a very rare example of a short sequence showing this kind of pseudo b-turn, [48] although it was observed in linear oligomers composed of repetitive a/b-units (e.g., Figure 7 c, d). This structure is in contrast to native bturns (Figure 7 b), which involve four residues to form the hydrogen-bonded structure in the opposite direction (residues 17 !4).…”
Section: Conformational Analysismentioning
confidence: 97%
“…This structure is in contrast to native bturns (Figure 7 b), which involve four residues to form the hydrogen-bonded structure in the opposite direction (residues 17 !4). To our knowledge, 10 a represents a very rare example of a short sequence showing this kind of pseudo b-turn, [48] although it was observed in linear oligomers composed of repetitive a/b-units (e.g., Figure 7 c, d).…”
Section: Conformational Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Both organic (from simple molecules to peptides and proteins) and inorganic complexes have been known for more than a century and are central to modern chemistry because of their fascinating, aesthetic architectures and multiple applications (Gan et al, 2011;Gellman, 1998;Thorat et al, 2013;Vijayadas et al, 2013;Ziach et al, 2018). Recently, coordination compounds have been reported that find applications in fields such as catalysis, gas storage, separation technology and molecular sensing (Mueller et al, 2006;Wan et al, 2006;Fé rey et al, 2003;James, 2003;Eddaoudi et al, 2002;Ruben et al, 2005, Kitagawa et al, 2004.…”
mentioning
confidence: 99%